PENGARUH MOTIVASI, KOMPLEKSITAS TUGAS, DAN INSENTIF MONETER TERHADAP KINERJA INDIVIDU - Azzardina, Aulia (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2021)
This study investigates the relationship between motivation and task complexity on performance. Monetary incentives are involved in this study as a moderating variable. The motivation examined in this research is intrinsic and extrinsic motivation. A 2x2 quasi-experiment has been conducted and involving 66 university students. Two and three-way ANOVA are used for hypothetical testing. The result shows that individuals with intrinsic motivation have shown better performance than those with extrinsic motivation. After individuals have faced more complex tasks, they achieved lower scores than those who faced less complex tasks. Prior studies suggested that motivation could be destructed by monetary incentives. However, there is no interaction proof when moderating variable is involved. The relationship between motivation and performance is not influenced by monetary incentives. In line with it, the relationship between task complexity and performance is also not strengthened or weakened by the given monetary incentives information. Thus, monetary incentives failed to influence the relationship between motivation, task complexity and performance.